2015
DOI: 10.1016/j.still.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of sediment source from a reservoir catchment in the black soil region, Northeast China

Abstract: A B S T R A C TAn understanding of long term temporal variations in sediment sources from a catchment is necessary to identify the major sources of sediment for effectively implementing soil conservation measures. For this purpose, a sediment column from Qixin reservoir and 410 samples from the three potential sediment sources were collected and radionuclides, soil organic carbon (SOC) and soil texture were analyzed. The relative contributions from different sources were determined using a simple mixing model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Linear gullies are a prominent feature of the study catchment, as demonstrated in Figures 1 and 8a. Several studies have reported that approximately 50% of the sediment originates from gullies, which is comparable with that from cultivated lands in the Mollisol region of northeastern China (Fang, 2015; Huang et al, 2020). This percentage increases to 90% during the rainy season (Chen et al, 2021), which is much greater than that reported in this study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Linear gullies are a prominent feature of the study catchment, as demonstrated in Figures 1 and 8a. Several studies have reported that approximately 50% of the sediment originates from gullies, which is comparable with that from cultivated lands in the Mollisol region of northeastern China (Fang, 2015; Huang et al, 2020). This percentage increases to 90% during the rainy season (Chen et al, 2021), which is much greater than that reported in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies on sediment provenance have also made important advancements in characterizing sediment transport in the Mollisol region of northeastern China. However, current research on sediment sources has focused almost exclusively on rainfall erosion or sediments collected from reservoirs (Fang, 2015; Huang et al, 2019; Huang et al, 2020), and research on the differences in sediment provenance between rainfall and snowmelt erosions is limited. In addition, the rapid development of intensive agricultural production systems has resulted in large inputs of synthetic fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the combined use of 137 Cs and 210 Pb ex as fingerprints in a small watershed in the Sichuan Hilly basin suggested that farmland and bare land are the two principal sediment sources for sediment samples collected from a downstream reservoir (Zhang et al, 2004). A combination of 137 Cs and 210 Pb ex was also applied to quantify sediment source contributions for reservoir sediment cores in a study area in northeast China with a cold climate (Fang, 2015). Geochemical fingerprinting carried out in a small catchment in the Three Gorges Reservoir Area suggested that dry farmland was a principal sediment source (Guo et al, 2014).…”
Section: Progress Of Sediment Source Fingerprinting Studies In Chinamentioning
confidence: 99%
“…Black soil has also been compared to "the giant panda of cultivated land". However, with the interaction of natural and human factors in the black soil area, soil erosion has become more and more serious, leading to the thinning of the black soil layer and the decrease of soil fertility [10]; coupled with a large amount of chemical fertilizer input and the scientific arable land management system is not perfect, leading to nutrient loss and water pollution [11][12][13]. At present, the surface soil of sloping arable land in black soil areas is lost at a rate of 2~3 mm�a -1 , and the organic matter content of the surface soil decreases at a rate of 5‰ per year.…”
Section: Introductionmentioning
confidence: 99%